Policies and Practices of Early Childhood Education and Care During the COVID-19 Pandemic: Perspectives From Five Countries - TORAN, MEHMET (Journal of Childhood, Education and Society, 2021)
The COVID-19 pandemic, which affects all areas of life, has also affected children in need of education and care. It is of great importance to develop policies that take into account the best interests of children in this process. In this review article, the policies developed for early childhood education and care during the pandemic period in five countries (Australia, Croatia, Hungary, Spain, and Turkey), how they are implemented, the problems that arose, and the solutions produced are discussed. As a result, the COVID-19 pandemic has revealed that we need to focus on eliminating the educational inequalities, set policies for the welfare of children on foundations that are more realistic, rebuild teacher training, and improve the welfare of families. Priorizating the best interests of the child in the policies to be developed and building the social ecology on justice will ease overcoming the crises that will be faced.
Bu yayın çok yazarlıdır. Kurum dışı yazarlar kayda dahil edilmemiştir. Yazarların tamamı tam metinde yer almaktadır.
Keywords: Covid-19; Pandemic; Early Childhood Education and Care; Policy; Practice; Children; Parents; Teachers